Geochemistry of post-collisional Yolcati (Bingol) volcanic rocks in Eastern Anatolia, Turkey - Kurum, Sevcan; Baykara, Tugce (Pergamon-Elsevier Science Ltd, 2020)
Yolcati volcanic rocks are products of the volcanic activities occurred in collisional and post collisional - post orogenic stages along the suture zone between the Anatolian and the Eurasian plates. The volcanic suite is made up of calk-alkaline to weakly alkaline basic-intermediate lavas and accompanying pyroclastics. Calk-alkaline lavas are basalts and andesites, and alkaline lavas are trachybasalt (hawaiite), trachyandesite (benmoreite) and trachyte in composition. SiO2 ratio ranges from 47,07% up to 67,18% and Mg# from 3,84% up to 52,67%. It is, principally, common that in the volcanic activity of spinel +/- garnet peridotite-type lower crust lithospheric (andesitic rocks) or asthenospheric (basic rocks) source, felsic rocks crystallised from a more heterogeneous magma compared to the mafic ones. Low Sr-87/Sr-86((i)) (0.7032559-0.7041843) and high Nd-143/Nd-144((i))) (0.512783-0.512927) ratios show a mantle source for lavas. Main petrologic characteristics and geochemical patterns indicate that these lavas are derived by the evolution of melts from primitive sources derived from the mantle source, and affected by a magmatic differentiation and fractional processes in different ratios. While the subduction-melts effect is apparent in basic rocks, more acidic rocks are thought to be the products of late-stage differentiation of magma, and the effect of continental enrichment in andesitic rocks are more pronounced, they point to the last stage of the magma crystallisation phase. All the petrographic and geochemical characteristics of Yolcati volcanic rocks are in concordance with the Eastern Anatolian Volcanic Provence Indicating that these volcanics may have been directly/indirectly affected by the regional tectonic processes (formation of Bitlis-Zagros Suture Zone and East Anatolian Fault Zone).
Keywords: Eastern anatolia; Yolcati volcanic rocks; Post-collisional volcanism; Geochemistry